Predicting Success on the ARRT National Certification Examination Through Mock Examinations. - Schmuck, Heather; Cook, Joy (Radiologic Science & Education, 2018)
The student pass rate on certification exams in the imaging sciences is important to programs and can impact accreditation. Being able to provide supplemental instruction prior to graduation would be possible if students could be identified as potentially unsuccessful. This study examined the relevance of a practice examination score as an indicator for success on the American Registry of Radiologic Technologists certification examination. Data from the practice examinations and participants' self-reported preliminary scores from the certification exam were matched and compared utilizing contingency tables. Sensitivity, specificity, positive predictive value, and negative predictive values were calculated for each tested parameter. While results lacked significance, the best cutoff score to be utilized as a threshold indicator for students who may need remediation prior to attempting the certification exam was 60. While this study was limited, programs could utilize this model to establish program specific thresholds for remediation and improve pass rates